Numerical Simulation and Experimental Research of Sheet Hemming Forming Based on Adhesive Filling - TANG Genglin, LI Jianjun, LI Yuanhui, ZHANG Longyao, ZHU Wenfeng (Shanghai Jiaotong Daxue xuebao, 2022)
The filling rate of adhesive is defined based on the geometric dimensions of the hemming model, and the numerical simulation model of the hemming process with adhesive is established by using the finite element method-smoothed particle hydrodynamics (FEM-SPH) method. By comparing and verifying with the hemming experiment with adhesive, the quantitative study of the influences of the hemming adhesive diameter, the edge distance, and the hemming thickness on the filling rate is realized. The research results show that the flow state and the final filling state of the adhesive layer obtained in the experiment are similar to the numerical simulation results, and the filling rate of the adhesive layer obtained in the experiment is highly consistent with the numerical simulation result, which verifies the feasibility and accuracy of the numerical simulation model. Further analysis shows that the influences of the hemming adhesive diameter, the edge distance, and the hemming thickness on the filling rate decrease in order, and the relationship formulas between the filling rate and process parameters, such as the hemming adhesive diameter, the edge distance, and the hemming thickness, are obtained by fitting, which provides a basis for the optimization design of the hemming process with adhesive of the automobile body sheet.